Human prostate cancer cells express neuroendocrine cell markers PGP 9.5 and chromogranin A. - Leiblich, A; Cross, S; Catto, J; Pesce, G; Hamdy, F; Rehman, I (2007)
BACKGROUND: A proportion of men with prostate cancer will progress to develop metastatic disease involving the lymph-nodes and bone. To identify novel candidates associated with metastatic progression, we compared the proteomic profiles of LNCaP (lymph-node metastatic, androgen-dependant) and PC-3 (bone metastatic, androgen-independent), human prostate cancer cells. METHODS: Two-dimensional polyacrylamide gel electrophoresis (2D-PAGE), followed by electrospray ionisation tandem mass spectrometry (ESI-MS/MS), was used to identify differentially expressed proteins. Western blotting was used to validate the identity of any candidates. Immunohistochemistry was used to assess tissue expression. RESULTS: 2D-PAGE followed by ESI-MS/MS analyses identified the expression of glutathione S-transferase-pi (GST-pi) and protein gene product 9.5 (PGP 9.5) in PC-3 cells, but absent expression in LNCaP cells. PGP 9.5 expression in PC-3 cells was confirmed by Western blotting, in addition to expression in DU145 cells. Analysis of cell conditioned media showed that PGP 9.5 was secreted. Sequencing of the PGP 9.5 gene promoter region in bisulfite modified DNA, suggested that the regulation of expression involves promoter hypermethylation. RT-PCR analysis for Chromogranin A (ChA) mRNA (a marker of neuroendocrine cells), showed expression in PC-3 and DU145 cells but was undetectable in LNCaP cells. Immunohistochemistry localised PGP 9.5 expression exclusively within neuroendocrine cells and nerve fibres. CONCLUSIONS: Our unexpected finding that the neuroendocrine cell markers PGP 9.5 and ChA are expressed by PC-3 and DU145 cells, suggests that these cells may have been derived from metastatic adenocarcinomas which had undergone neuroendocrine differentiation or alternatively the expression occurred ectopically as a result of cell culture.